2019
DOI: 10.1080/17515831.2019.1576449
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high-quality rare earth oxide modified resin-based brake material

Abstract: A high-quality brake material was developed by using different rare earth oxide modified resinbased brake materials and designing the composite material through an orthogonal optimization test. The effect of rare earth oxide on the properties of the resin-based brake material, such as the friction and wear, thermal decay resistance, and recovery, was explored using the constant-speed friction test, Chase friction test and worn surface morphological observation. The results show that rare earth lanthanum oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The features of resin-based friction materials ensure a simple process, low cost, and strong structure. The material is now the most in-demand class of composite material [ 3 , 4 ]. A friction material is usually a composite material made up of a combination of more than 10 components.…”
Section: Introductionmentioning
confidence: 99%
“…The features of resin-based friction materials ensure a simple process, low cost, and strong structure. The material is now the most in-demand class of composite material [ 3 , 4 ]. A friction material is usually a composite material made up of a combination of more than 10 components.…”
Section: Introductionmentioning
confidence: 99%
“…Such materials can meet the highest requirements for both mechanical and tribological properties [ 19 , 20 , 21 ]. Phenolic-based nanocomposite brake friction pads are preferred due to their durability in dry friction and resistance in harsh environments [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the doping of rare earth elements can significantly improve the tribological properties of phenolic-based hybrid nanocomposites [ 19 , 22 , 24 , 25 ]. Yu et al designed a kind of polyimide nanocomposite filled with different rare earth oxides based on carbon nanotubes and graphene oxide, finding that filling with cerium oxide can dramatically reduce the friction coefficient and wear rate [ 19 ].…”
Section: Introductionmentioning
confidence: 99%